Toxicity and Disease-Related Outcomes after Radiotherapy for Head and Neck Cancer in Human Immunodeficiency Virus-Positive Patients - Grew, David J.; Cooper, Benjamin T.; Nguy, Susanna; Halperin, Jason; Sanfilippo, Nicholas J. (Frontiers in Oncology, 2014)
Background: Human immunodeficiency virus (HIV) seropositivity may be associated with higher risk of local recurrence and poor survival in multiple malignancies. However, long-term disease control in HIV-positive patients with head and neck cancer (HNC) is not well described. The purpose of this study is to review the disease-related outcomes of HIV+ patients who underwent radiotherapy (RT) or chemoradiotherapy (CRT) at our institution. Methods: We retrospectively reviewed 24 HIV-positive patients who underwent radiotherapy (RT) for HNC between 2004 and 2013. Patient characteristics, treatment details and outcomes were collected. Overall survival (OS) and local recurrence-free survival (LRFS) was investigated. Kaplan-Meier estimated survival was calculated. Results: Median follow-up was 21 months. All patients were treated with curative intent. Eighty-three percent had stage III-IV. Primary sites of disease included oropharynx (n=12), larynx (n=6), oral cavity (n=2), unknown primary (n=2), nasal cavity (n=1), and paranasal sinuses (n=1). Four patients (17%) had definitive RT alone and 9 definitive CRT (38%; 8 cisplatin and 1 cetuximab). Eleven (46%) were treated in the adjuvant setting after surgical resection; 6 with RT alone and 5 with concurrent cisplatin. Eight patients had acute Grade 3 toxicity with no acute Grade 4 or 5 toxicities. Fifteen patients (63%) were alive and disease-free. 2 and 5-year OS was 67% and 59%. LRFS at 2-years was 82%. Median OS was 83 months. Conclusions: In this cohort, HIV-positive patients treated aggressively with curative intent had excellent overall survival and local control following RT or CRT for HNC. Treatment was relatively well-tolerated compared to historical controls. This group of patients should be managed aggressively with intent to cure.